Russian bond market: the problems of the disclosure system - A. P. Andreev (Путеводитель предпринимателя, 2020)
Currently, there is a number of problems that prevent the development of the Russian securities market. This article examines the problems of information provision of the bond market and suggests the ways to address them in order to increase the attractiveness of the Russian securities market for investors. The object of the study is the disclosure system on the Russian bond market. The subject of the study is the regulatory requirements for disclosure of information and the types of liability for incorrect disclosure of information in Russia. The author of the article conducts a study of the information disclosure system on the Russian bond market using such methods as observation, analysis and synthesis.